Pengaruh Asimetri Informasi, Leverage, dan Ukuran Perusahaan Terhadap Praktik Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013) - Yamaditya, Vanian; Raharja, Raharja (Diponegoro Journal of Management, 2014)
This study aims to investigate the influence of information asymmetry, leverage, and firm size on earnings management practices in manufacturing companies listed on the Stock Exchange. This study took populations companies listed on the Indonesia Stock Exchange (IDX) 2011-2013. The sampling technique used was purposive sampling method. The method of analysis used in this study using multiple linear regression analysis to examine the effect of information asymmetry, leverage, and firm size on earnings management practices. The variables used in this study is the asymmetry of information, leverage, and firm size as an independent variable; earnings management practices as the dependent variable. The results showed that the asymmetry of information and firm size has positive influence on earnings management practices, but leverage has no effect on earnings management practices.